Does seasonal vulnerability to poverty matter? A case study from the Hadejia-Nguru Wetlands in Nigeria - Levison Chiwaula; Hermann Waibel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Applying research on vulnerability to seasonal data, we assess seasonal vulnerability to poverty using panel data from the Hadejia-Nguru Wetlands in Nigeria involving 260. We find that both observed poverty and vulnerability to poverty vary seasonally and that these variations are related to household livelihood strategies. Basing on our findings policy interventions should aim at increasing crop productivity (both food and cash crops) and returns to crop sales as well as promoting income diversification to off-farm activities. Safety net programs should be implemented only after productivity-enhancing interventions have been implemented. Further research is proposed to particularly assess the influence of seasonal variation on household livelihood choices.
Keywords: 330; Vulnerability to poverty; Seasonality; Social protection; Nigeria